The Influence of Personality, Emotional Intelligence and Affective Commitment on Employees Performance at The Head Office of PT. Indah Logistik Cargo Yogyakarta - Abrar, Althaf; Hikmah, Khoirul (CV. Strata Persada Academia, 2025)
This study aims to analyze the influence of personality, emotional intelligence, and affective commitment on employee performance at the Head Office of PT. Indah Logistik Cargo Yogyakarta. The research is grounded in the importance of psychological and organizational approaches to improving employee performance, particularly in the context of complex workplace dynamics caused by generational, age, and cultural diversity. A quantitative approach with a descriptive-causal method was employed. The sample consisted of 34 respondents, selected through a saturated sampling technique involving all employees at the head office. Data were collected through structured questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS software. The results indicate that, partially, personality and emotional intelligence have a significant influence on employee performance, with significance values of 0.007 and 0.000, respectively (< 0.05). In contrast, affective commitment does not have a significant partial effect (p = 0.367). However, when tested simultaneously, all three variables have a significant influence on employee performance, as indicated by an F-value of 10.868 and a significance level of 0.000. These findings suggest that personality management and emotional intelligence development should be prioritized in human resource management strategies. This study contributes theoretically to the literature on workplace behavior and provides practical implications for enhancing employee effectiveness in the logistics sector. Future research is recommended to incorporate additional variables such as work motivation, work environment, and compensation systems to gain a more comprehensive understanding of the factors influencing employee performance.